2016
DOI: 10.3390/v8010016
|View full text |Cite
|
Sign up to set email alerts
|

Rhinoviruses and Respiratory Enteroviruses: Not as Simple as ABC

Abstract: Rhinoviruses (RVs) and respiratory enteroviruses (EVs) are leading causes of upper respiratory tract infections and among the most frequent infectious agents in humans worldwide. Both are classified in the Enterovirus genus within the Picornaviridae family and they have been assigned to seven distinct species, RV-A, B, C and EV-A, B, C, D. As viral infections of public health significance, they represent an important financial burden on health systems worldwide. However, the lack of efficient antiviral treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
112
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(130 citation statements)
references
References 188 publications
4
112
1
9
Order By: Relevance
“…Our study monitored circulation of RVs over a relatively long time period, which allowed us to examine the circulation of RV species and types over 6 years, thereby limiting the influence of single outbreaks. Our observation that RVs circulate during the whole year has been found repeatedly [1,8]. Interestingly, Linder et al also reported a dominance of RV-C in the winter months [30].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our study monitored circulation of RVs over a relatively long time period, which allowed us to examine the circulation of RV species and types over 6 years, thereby limiting the influence of single outbreaks. Our observation that RVs circulate during the whole year has been found repeatedly [1,8]. Interestingly, Linder et al also reported a dominance of RV-C in the winter months [30].…”
Section: Discussionsupporting
confidence: 75%
“…The same holds true for EV-C104, which was detected in five samples (from four infections). The other EVs detected are found only occasionally in respiratory samples [8,29].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Human enteroviruses are the most prevalent viral pathogens which produce diseases ranging from asymptomatic infections to deadly syndromes . Using current clinical diagnostics and respiratory surveillance methodologies, rhinoviruses, and enteroviruses are not often identified to the species level.…”
Section: Discussionmentioning
confidence: 99%
“…Picornaviruses of the genus Enterovirus (EV) comprise many human pathogens that cause most common infections in humans, such as EV A-D and rhinovirus (RV) A-C [1]. The EVs are small, single-stranded, positive-sense RNA viruses with a genome of ~7.5 kb, encapsidated into an icosahedral capsid, forming a non-enveloped virion of around 30 nm diameter.…”
Section: Introductionmentioning
confidence: 99%